Saluran Pemasaran dan Daya Serap Lembaga Pemasaran Jagung Varietas Bisi-2 di Kabupaten Muna - Sinaini, La; Baru, La (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2020)
Corn marketing is the activity of distributing corn production from farmers to consumers. Corn production produced by farmers is not of economic value if the production of corn does not reach the hands of consumers. Corn marketing creates a price difference between what farmers receive and the price that consumers receive. This is due to the involvement of middlemen/traders of corn production from the hands of farmers in the hands of consumers. The purpose of this study was to analyze the marketing channels and absorptive capacity of Bisi-2 corn marketing institutions in Muna District. This research was conducted from January 2019 until May 2019 in Kabangka sub-district. The research location is one of the corn production centers of Bisi-2 varieties in Muna District. Sources of data in this study are primary data obtained directly from informants. The selection of informants used snowball sampling technique with the number of informants being 10 village collector traders, 1 sub-district trader collector, 5 animal feed traders, and 3 breeders. Data is collected by cross-section. Analysis of the data used in this study is qualitative descriptive analysis. Research results show the marketing channel for corn in Muna District, there are five patterns, namely; (1) marketing channels (farmers - village collector traders –sub-district collector traders - corn collecting companies); (2) marketing channels (farmers - village collector traders –sub-district collector traders - animal feed traders - breeders); (3) marketing channel (farmer - village collector trader - rancher) and (4) marketing channel (farmer - rancher). The marketing channel (farmer - village collector trader –sub-district collector trader - corn collecting company) is a channel that absorbs corn production the largest in Kabangka District, Muna District.